PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING MENGGUNAKAN MAKET PONDASI CAKAR AYAM PADA ELEMEN KONSTRUKSI DAN UTILITAS GEDUNG UNTUK MENINGKATKAN HASIL BELAJAR KELAS XI DPIB DI SMK NEGERI 2 MEDAN - Dea Fani Romatua Hasibuan1; Liana Atika, S.Pd., M.Pd; Prof. Dr. Harun Sitompul, M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve students' learning outcomes through the implementation of the Project Based Learning (PjBL) model using a Chicken Claw Foundation Model in the Construction and Building Utilities subject for Class XI DPIB 2 at SMK Negeri 2 Medan in the 2025/2026 academic year. This research employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The research subjects were 35 students of Class XI DPIB 2. Data were collected through classroom observations, learning achievement tests, project assessments, and documentation. The data were analyzed using descriptive quantitative techniques by calculating the mean scores, classical learning mastery percentages, and the improvement in learning outcomes across the two cycles. The results indicated that the implementation of the Project Based Learning model using a Chicken Claw Foundation Model successfully improved students' learning outcomes. The average learning score increased from 59.90 in Cycle I to 78.00 in Cycle II. Furthermore, the classical learning mastery improved from 0% in Cycle I to 71.42% in Cycle II. The hypothesis testing also indicated a significant improvement in students' learning outcomes after implementing the Project Based Learning model using the Chicken Claw Foundation Model. Therefore, the Project Based Learning model assisted by the Chicken Claw Foundation Model is effective in improving students' learning outcomes in the Construction and Building Utilities subject for Class XI DPIB 2 at SMK Negeri 2 Medan.